(untitled) (Ustozlar uchun, 2026)
This article explores various Cultural Anthropology aspects of customs, traditions, and festivals around the world. Customs and traditions play an important role in shaping the cultural identity of societies and reflect the values, beliefs, and historical experiences of different communities. Throughout history, people from different regions have developed unique cultural practices that help preserve their heritage and strengthen social bonds within their communities. Festivals, rituals, and traditional ceremonies are among the most visible expressions of these cultural customs.The article discusses how traditions are passed from one generation to another and how they help maintain a sense of belonging and cultural continuity. In many countries, festivals are celebrated to mark important historical events, religious beliefs, seasonal changes, or national achievements. These celebrations often include music, dance, traditional clothing, special foods, and communal gatherings. Such elements make festivals not only cultural events but also important social occasions that bring people together.